Redox-Dependent Modulation of Anthocyanin Biosynthesis by the TCP Transcription Factor TCP15 during Exposure to High Light Intensity Conditions in Arabidopsis. Issue 1 (16th November 2015) - Viola, Ivana L.; Camoirano, Alejandra; Gonzalez, Daniel H.
Abstract : The transcription factor TCP15 represses anthocyanin biosynthesis in a redox-dependent manner during high-light intensity conditions. Abstract: TCP proteins integrate a family of transcription factors involved in the regulation of developmental processes and hormone responses. It has been shown that most members of class I, one of the two classes in which the TCP family is divided, contain a conserved Cys that leads to inhibition of DNA binding when oxidized. In this work, we describe that the class-I TCP protein TCP15 inhibits anthocyanin accumulation during exposure of plants to high light intensity by modulating the expression of transcription factors involved in the induction of anthocyanin biosynthesis genes, as suggested by the study of plants that express TCP15 from the 35SCaMV promoter and mutants in TCP15 and the related gene TCP14 . In addition, the effect of TCP15 on anthocyanin accumulation is lost after prolonged incubation under high light intensity conditions. We provide evidence that this is due to inactivation of TCP15 by oxidation of Cys-20 of the TCP domain. Thus, redox modulation of TCP15 activity in vivo by high light intensity may serve to adjust anthocyanin accumulation to the duration of exposure to high irradiation conditions.